Performance of lightweight foamed concrete using laterite as sand replacement - Khaw, Yong Hui (2010)
Lightweight foamed concrete (LWC) has been successfully used and it has gained popularity due to its lower density than conventional concrete. It is created by uniform distribution of air bubbles throughtout the mass of concrete. Recently, most studies on LWC concern on the influence of filler type and the particle size of sand on the strength. In this study, the strength of LWC with density 1400 kg/m 3 was produces due to different percentage of laterite as sand replacement. Four series of LWC mix designs with ratio 2:1:1 comprises of 0%, 5%, 10% and 15% as sand replacement (by total weight of sand) were considered. Two types of testing were conducted namely compressive strength and modulus of elasticity (MOE). The tests were prepared in order to determine the effect of using different percentage of laterite due to different curing ages. The results revealed that, increasing the percentage of laterite as sand replacement, the strength improves significantly due to compressive strength and MOE for all mixes. It also indicated that the curing ages significantly affect its strength. However, it is noted that the optimum mix design to produce LWC-Laterite was obtained by using 5% of laterite as sand replacement.